MY FAMILY OF TEACHERS AND MY DREAM OF BECOMING AN ENGLISH TEACHER - Azizova Shirin Abdulhamid qizi (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation. This article is a heartfelt narrative written by Ogiloy, a 6th-grade student from Uzbekistan, who comes from a family of dedicated teachers. She shares her admiration for her family's passion for education and their impact on her decision to pursue a career as an English teacher. Ogiloy explains her love for the English language, its global importance, and her desire to contribute to her community by improving education in Uzbekistan. Her story highlights the influence of her family's teaching legacy and her commitment to making a positive difference in the lives of future students.